Asylum seekers and refugees in the contemporary world - Whittaker, David J., 1925-2017 (Making of the contemporary world., 2006)
Examining a number of case studies, including Palestinian, Afghan and Iraqi refugees, David J. Whittaker's book provides a balanced introduction to this very controversial subject. Fuelled by extensive coverage in the media, the issue of asylum seekers and refugees is one of the most talked about subjects in contemporary politics. Whittaker cuts through the emotive language to give an objective introduction to the subject. Asylum Seekers and Refugees in the Contemporary World discusses the international as well as national implications of the issue, and the book looks.